Reassessment of pneumatic retinopexy for primary treatment of rhegmatogenous retinal detachment - Cohen, Eyal (Clin Ophthalmol, 2015)
BACKGROUND: Pneumatic retinopexy (PR) remains a popular technique for the treatment of rhegmatogenous retinal detachment (RRD). OBJECTIVE: To evaluate the single operation and final success rate of PR for primary treatment of RRD and to determine factors associated with anatomical and visual outcomes. METHODS: This retrospective case review study analyzed the data of patients who underwent PR for primary treatment of RRD. Patients with a follow-up period of <2 months were excluded. Single operation success was defined as successful retinal reattachment following a single PR throughout 2 months of follow-up. RESULTS: Eighty-four eyes met the inclusion criteria. Single operation success was achieved in 50 eyes (59.5%), while 82 obtained anatomical success at the final follow-up visit (97.6%). An average of 0.702±1.095 additional retinal detachment operations was necessary to achieve final anatomical success in the entire cohort (n=84) and 1.4±1.3 in the single operation failure group (n=34). Both groups (single operation success vs failure) did not differ significantly in any of the preoperative variables. Multivariate analysis of pseudophakic patients (n=22) revealed that 52.65% of the variation in single operation outcome was explained by the number of clock-hours detached (partial R(2)=43.76%, P=0.001). The final best-corrected visual acuity was significantly better in the single operation success group (logarithm of minimum angle [logMAR] 0.229±0.249 vs logMAR 0.747±0.567, P<0.001). CONCLUSION: Careful patient selection is warranted before performing PR in RRD, particularly in pseudophakic patients with large detachments. Ultimately 60% of the cases will attach after the procedure with the rest requiring on average 1.4 additional procedures to achieve final anatomical success.